Desmoglein-3 autoantibodies in tissues of oral lichen planus patients and its correlation with disease severity: case-control study - Doaa Abdelwadood; Yasmine Ahmed Fouad; Nashwa El-Khazragy; Ahmed Elsayed Hamed Amr (BMC Oral Health)
Abstract Background Due to the not fully understood exact pathogenesis of oral lichen planus, the patients receive symptomatic management, rather than a curative treatment. Consequently, revealing the pathogenesis of OLP is a primary concern in oral medicine research. Elevated levels of circulating antibodies against Desmoglein 3 have been discovered in the serum of OLP patients. The aim of the present study was to evaluate the level of Desmoglein 3 autoantibodies in tissue biopsies of atrophic/bullous erosive OLP and to correlate it with the disease severity, in attempt to reveal if it has a role in the pathogenesis of the disease. Methods This is a case-control study, tissue biopsies were obtained from clinically and histopathologically diagnosed atrophic/bullous-erosive oral lichen planus (OLP) lesions (n = 10). The oral lichen planus biopsies were compared with healthy uninflamed gingival tissues excised during periodontal surgeries (n = 10). The tissue biopsies were tested for quantitative levels of desmoglein 3 autoantibodies using ELISA test. The clinical severity of oral lichen planus lesions was evaluated by Elsabagh scoring system. The levels of desmoglein 3 autoantibodies were correlated with the disease severity. Results The concentration of desmoglein 3 autoantibodies level in tissues of patients with atrophic/erosive OLP [3395.4 (± 526.9) Pg/g] was significantly higher (p < 0.001) than in tissues of healthy controls [2329.7 (± 307.6) Pg/g]. The student’s t-test was used to compare between the two groups. Moreover, the concentration of desmoglein 3 autoantibodies showed a statistically significant positive correlation (ρ = 0.801) with OLP clinical severity scores (p = 0.005). Conclusions Desmoglein 3 autoantibodies were detected in higher concentrations in oral lichen planus tissues compared to healthy controls. Increased concentration of desmoglein 3 autoantibodies is correlated with an increase in oral lichen planus clinical severity scores and vice versa. So, further investigation is needed to discover the exact role of Dsg3 autoantibodies in the pathogenesis of OLP. Trial registration The study was registered on the Clinical Trial Registration Site (registration code: NCT06652477, last updated on 22-10-2024).